(untitled) (Indian Journal of Arid Horticulture, 2025)
Guava (Psidium guajava L.), a common man’s fruit commonly called the "apple of the tropics" is cultivated or grown wild throughout the tropical and subtropical regions of the world. India’s output of guava increased from 10.15 lakh tonnes in 1989-90 to 16.85 lakh tonnes in 2004-05. The area rose from 1.03 lakh ha. to 1.62 lakh ha. with a yield of 11.10 tha’. Guava is one of the richest sources of vitamin C (200 to 400 mg per 100g fresh weight) and some cultivars are also rich in vitamin A. Guava fruit consists of about 20% peel, 50% fleshy portion, and 30% seed core. It contains 74-87% moisture, 13-26% dry matter, 0.8-1.5% proteins, 0.4-0.7% fat, and 0.5-1.0% ash. It is one of favourite fruit, which can be utilized for processing however selection of guava varieties for processing depends on several factors such as content of pulp, seeds, sugars, acids, pectin, and tannins in the fruit. The guava fruit can be consumed fresh; processed into a semiproduct in the form of puree, clarified juice, or concentrate and frozen or aseptically stored; or processed continuously to the final products, which include nectar, syrup, jam, jelly, fruit bar, cheese, chutney, ketchup, wine, dried fruit and powder, as well as canned guavas. Among them, guava nectar is more important than the others in the quantity of production and the popularity among consumers. The fruits of Sardar variety yield high-grade pectin with higher jelly units than the fruits from other varieties. Juice obtained from fresh fruits or from pulp can be used in the manufacture of clear guava nectar, clear guava juice blend, clear guava jelly, or guava powder.